RESPONS SEISMIK DI KECAMATAN MUARA BANGKAHULU, KOTA BENGKULU MENGGUNAKAN KONSEP PERAMBATAN GELOMBANG - Rena Misliniyati; Muhammad Farid; Khairul Amri; Lindung Zalbuin Mase; Fepy Supriani (LPPM Universitas Negeri Jakarta, 2024)
The position of Bengkulu Province, which is flanked by the subduction zone between the Euro-Asian and Indian-Australian plates to the west, and the Sumatra Fault zone to the east, makes Bengkulu City one of the areas prone to earthquake disasters. Muara Bangkahulu District is one of the sub-districts in Bengkulu City. Muara Bangkahulu sub-district is an area that functions as a government centre, trade and service centre, and one of the education centres in Bengkulu City. This study aims to determine the ground response in the Muara Bangkahulu sub-district area during an earthquake. The wave propagation method used in this study is a one-dimensional equivalent of linear and nonlinear modelling that propagates earthquake waves from bedrock to surface. The results of this study are Peak Ground Acceleration (PGA), amplification factor, earthquake acceleration time history, and acceleration spectra response. The results of this analysis will be compared between equivalent linear and nonlinear values. The results of this study can also help us realise and further consider the value of seismic design in the Muara Bangkahulu sub-district area, mainly if a stronger earthquake occurs in the future.